Gambaran Faktor-Faktor Tidak Langsung Pada Kejadian Stunting di Wilayah Kerja Puskesmas Cijulang Kabupaten Pangandaran - Balqis, Pamela; Windani Mambang Sari, Citra (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Stunting is a condition of chronic malnutrition where a toddler's height is shorter than they age. There were 63 cases of stunting in Cijulang District. Stunting prevention can be implemented by modifying indirect factors. The study aimed was to identify indirect factors in the incidence of stunting in the working area of the Cijulang Health Center, Pangandaran Regency. Methods: This research is in the form of quantitative descriptive with total sampling technique of 63 sample. The research instrument used a demographic data questionnaire, the Household Food Insecurity Assessment Scale (HFIAS) and the Parental Feeding Style Questionnaire (PFSQ) which have been declared valid and reliable. The research was analyzed by univariate analysis. Results: Based on the identification of indirect factors in the incidence of stunting, most of the children came from families with a little food insecurity (61.9%), neglected parenting (31.3%), mother's education in junior high school/equivalent(41.3%), and family income <Rp.1,884,364 (76.2%). Conclusion: Nurses are expected to assist to mother of toddlers regarding toddler nutrition knowledge. In addition, the health service also strives for mothers and families of toddlers to pay attention to exclusive breastfeeding, maintenance of environmental sanitation and routine check-ups during pregnancy.